Triglyceride-glucose index and periodontitis: evidence from two population-based surveys - Huang, Jing; Zhang, Dan; Li, Hua; Zhang, Yiyun; Long, Tianxue; Guo, Xiaojing; Cui, Hangyu; Wei, Zixuan; Zhao, Jun; Li, Mingzi; Wang, Pangbo (Frontiers in Endocrinology, 2025)
BackgroundThe relationship between the Triglyceride-Glucose (TyG) index and periodontitis remains unclear. This study aims to elucidate this relationship using data from two large population-based surveys.MethodsDatasets from NHANES (2009-2014) and KNHANES (2007-2018, except for 2011) were utilized. We applied multivariate logistic regression, stratified analysis, restricted cubic splines (RCS), and subgroup analyses to examine the correlation between the TyG index and periodontitis risk. The predictive value of the TyG index was assessed using receiver operating characteristic (ROC) curves. Mediation analyses investigated variables mediating this relationship.ResultsThe NHANES and KNHANES cohorts included 2,511 and 16,239 participants with periodontitis, respectively. After adjusting for covariates, the TyG index was significantly associated with periodontitis risk (NHANES: OR 1.19, 95%CI: 1.07-1.34; Q2 vs. Q1, OR 1.20, 95% CI: 1.02-1.42; Q4 vs. Q1, OR 1.23, 95%CI: 1.02-1.49. KNHANES: OR 1.09, 95% CI: 1.05-1.13; Q4 vs. Q1, OR 1.09, 95%CI: 1.02-1.17, P for trend = 0.025). RCS analyses revealed a nonlinear relationship. ROC curves indicated that the predictive values of the TyG index were 8.24 (NHANES) and 8.69 (KNHANES). Mediation analysis showed that inflammatory (alkaline phosphatase and white blood cell) and metabolic factors (vitamin D and high-density lipoprotein cholesterol) partially mediated this association.ConclusionsThe observational analysis reveals a significant association between the TyG index and the risk of periodontitis. Further studies are needed to clarify the underlying mechanisms.